hCLE/RTRAF-HSPC117-DDX1-FAM98B: A New Cap-Binding Complex That Activates mRNA Translation - Pazo, Alejandra; Pérez-González, Alicia; Oliveros, Juan Carlos; Huarte, Maite; Chavez, Juan Pablo; Nieto, Amelia (Frontiers in Physiology, 2019)
hCLE/C14orf166/RTRAF, DDX1 and HSPC117 are components of cytoplasmic mRNA-transporting granules kinesin-associated in dendrites. They have also been found in cytoplasmic ribosome-containing RNA granules that transport specific mRNAs halted for translation until specific neuronal signals renders them accessible to the translation machinery. hCLE associates to DDX1, HSPC117 and FAM98B in HEK293T cells and all four proteins bind to cap analog-containing resins. Competition and elution experiments indicate that binding of hCLE complex to cap resins is independent of eIF4E; the cap-binding factor needed for translation. Purified hCLE free of its associated proteins binds cap with low affinity suggesting that its interacting proteins modulate its cap association. hCLE silencing reduces hCLE accumulation and that of its interacting proteins and decreases mRNA translation. hCLE-associated RNAs have been isolated and sequenced; RNAs involved in mRNA translation are specifically associated. The data suggest that RNA granules may co-transport RNAs encoding proteins involved in specific functions together with RNAs that encode proteins needed for the translation of these specific RNAs and indicate an important role for hCLE modulating mRNA translation.